Pendidikan Islam Menurut Imam Al-Mawardi - Ade Wahidin (At-Tajdid: Jurnal Ilmu Tarbiyah, 2018)
Islam as a perfect and comprehensive religion, greatly emphasizes its adherents to explore the sciences related to Islam. Whether the science is categorized as the science of al-Ghāyah (Science of goals such as Tawhid, Tafsir, Hadith, etc.) or categorized as the science of al-Wasīlah (Intermediary science, such as science Nahwu, Sharaf, Balaghah, etc.). Therefore, it is not surprising that Islam from time to time continue to give birth to the experts of religion that has the competence quite varied and comprehensive. In addition, not a few among the Muslim scholars who left the monumental works in various disciplines that are very influential for the civilization of Muslims in particular and for mankind in general. Among Muslim scholars who are interesting to study his thoughts are Imam al-Marwardi, especially related to his education which conceptually refers to the Qur'an and Hadith and Ijma 'the Companions of the Prophet. The concept of Islamic education which he initiated can be a valuable treasure for later generations, especially related to the concept associated with the criteria of the learner and educator ideal.